Growth and yield parameters of white oat and wheat as affected by canola residue - Fioreze S.L. (2019)
© 2019 Universidade Federal de Vicosa.Despite being an important crop option for Brazilian agriculture, canola has some characteristics that may limit its insertion in some cropping systems, such as its allelopathic effects. Thus, the present work aimed to study the effect of canola crop residues on the seed germination, growth and grain yield of white oat and wheat plants. In laboratory conditions, white oat (Milton) and wheat (Tbio Pioneiro) seeds were germinated in the presence of aqueous extracts of (i) aboveground part, (ii) root system, (iii) whole plant and (iv) twice the concentration of the whole plant extract, besides a control. In green house conditions, the same oat and wheat cultivars were grown until harvest, on soil mixed with fresh canola crop residues (whole plant residues, aboveground residues and root residues) and a control. Aqueous extract of the whole canola plant reduced the germination and increased abnormal seedlings of white oat and wheat, mainly in high concentration. For soil crop, the presence of canola residues did not affect the white oat emergence, growth and grain yield. For wheat, plant emergence was lower in the presence of canola residues, but growth and yield were not affected.